Potensi beta-glukan sebagai pakan imbuhan pada ayam broiler: Reviu - Listya Purnamasari; Joseph F. dela Cruz; Kim Jesserene V. dela Cruz (Jurnal Ilmu Peternakan Terapan, 2022)
Poultry as an industry was continuously growing worldwide and demands for poultry meats were markedly increasing. However, the limited use of antibiotics as treatments and as growth promoters became a serious problem due to the emergence of antibiotic resistance. Therefore, exploring other alternatives such as using feed additives like beta-glucans were widely studied and used to meet the demands of the consumers. This review focused on the different functions and effects of beta-glucans in poultry. Beta-glucans were known to have immunomodulation effects by upregulating the cytokines and other immune cells to overcome a disease. Aside from its immunomodulation effects, it can also increase the intestinal villi and crypts. Furthermore, an increase in growth performance was also observed. This evidence is promising but further research is required to properly establish the various functions of beta-glucans in poultry.